Therapeutic effect of chitosan modification on salmon-calcitonin-loaded PLGA nanoparticles - Lee, Min-Jeong; Seo, Da-Young; Lee, Hea-Eun; Choi, Guang Jin (The Korean journal of chemical engineering, 2011)
Although salmon-calcitonin (sCT) has been known as a potent drug for the treatment of osteoporosis, its oral dosage form products have not been commercially available primarily due to a poor oral bioavailability. Chitosan has been extensively examined as a potential oral absorption enhancer, whereas encapsulation with PLGA has been widely studied to address the delivery problems of typical peptide drug molecules. We investigated the mechanism and therapeutic effect of chitosan modification on the sCT-loaded PLGA nanoparticles. Chitosan was added onto these particles in two ways: by incorporation during W/O/W emulsification and by solid dipping. Particles were characterized by particle size analyzer, Zeta potential analyzer, scanning electron microscopy, and so forth. Nano-sized particles of 430–590 nm in fairly spherical shape with a narrow size distribution were produced. The PLGA encapsulation efficiency greater than 50% of added sCT was achieved regardless of chitosan modification. It turned out that sCT-loaded PLGA particles with chitosan modified during W/O/W emulsification (referred to as sCT-PLGA-CHT1) showed better therapeutic behavior in terms of sustained release effects as well as short-period hypocalcemic effects than the others. It was concluded that the beneficial effect was greatly associated with the formation of embedded structure of chitosan molecules when particles were modified with chitosan.